(untitled) (Nigerian Journal of Technology, 2017)
This paper evaluated selected solutions of moment method in respect to Biochemical Oxygen Demand (BOD) kinetics with the aim of ascertain error free solution. Domestic-institutional wastewaters were collected two-weekly for three months from waste-stabilization ponds in Obafemi Awolowo University, Ile-Ife. BOD concentrations (BODc) were determined daily for 8 days using standard method. The BODc were used to determine parameters in BOD kinetics (ultimate BOD concentration and BOD removal rate) using Microsoft Excel Solver, non-linear regression (exponential) and least squares methods (three graphs). Accuracies of these solutions were evaluated using relative error, Akaike Information Criterion (AIC), and model of selection criterion (MSC). The study revealed that ultimate BODc was in the range of 1368.7 to 860.6 mg/L and BODc removal rate was between -0.139 and -0.470 /d. The averages of MSC were 4.18; 0.01; 1.49, 1.28 and 1.61 for Microsoft Excel Solver, non-linear and three least square methods (graphs 1, 2 and 3) respectively. The result revealed that Microsoft Excel Solver provided an improved solution of moment method, and a good description of BODc removal trend based on MSC and AIC than the other solutions. The study concluded that Microsoft Excel Solver solution to the method is a valuable solution at higher confidence level based on lower values of AIC and high values of MSC. http://dx.doi.org/10.4314/njt.v37i1.1